Patriarchal oppression in palestinian society through the institution of marriage in the novel of Noble Origins by Sahar Khalifeh - Priyanka Priyanka, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The institution of marriage prescribes different norms for men and women. Patriarchal and heterosexual marriage expects husband and wife to follow their set gender roles which is an inseparable part of this institution. It works in a hierarchy. The Palestinian novelist Sahar Khalifeh, who hails from the West Bank, condemns the hypocrisy of the institution of traditional marriage that oppresses women in Arab society. In her literary narratives, Khalifeh portrays the traditions and customs of Arab society which act as weapons of oppression against women. In her works, she demonstrates that it is the customs and traditional practices imposed on women that are oppressive rather than religion. The objective of the paper is to dissect the way in which the institution of marriage largely supports and upholds the patriarchal and neopatriarchal values even in an ostensibly revolutionary population such as the Palestinian society by focusing on one of the Arabic novels of Khalifeh - Of Noble Origins translated into English. This paper examines the patriarchal norms of male dominance in public spheres and also highlights how the Palestinian women resist these sexist ideologies prevailing in their society. Thus, the study of Khalifeh’s narratives in this paper is two-pronged: first, to analyse how male domination works, and second, to scrutinize how the women in her novels find ways to respond to the multi-level patriarchal domination. The paper includes a theoretical framework comprising patriarchy, neopatriarchy and male gaze. Keywords: patriarchy; neopatriarchy; gender discrimination; institution of marriage; Sahar Khalifeh